IS IT TRANSPARENT AND ACCOUNTABLE, OR JUST STEAL THE PUBLIC ATTENTION? - rafles ginting (Jurnal Akuntansi, 2023)
This study aims to find out how the implementation of transparency carried out by schools related to financial reporting and BOS funds to third parties and to analyse how the accounting system applied to school financial reporting and BOS Funds is compared to the provisions in accordance with Statement of Financial Accounting Standards (ISAK) 35 and technical guidelines related to BOS Funds imposed by the Ministry of Education, Culture, Research, and Technology. In this study, researchers conducted an analysis by collecting data, compiling it. interpret and analyse the data to produce research conclusions. This type of research is descriptive qualitative research through centralized interviews with informants to obtain accurate and relevant data. The results of this study show that the reporting of the school BOS Fund has been carried out, but the financial statements made by the school are still not in accordance with ISAK 35